Glazed Ceramics from Qaraqorum: Archaeological Evidence on Routes to the Old-Mongolian Capital - Sklebitz, Anne (Acta Mongolica, 2022)
The Old-Mongolian capital Qaraqorum is described in historical sources as a vivid, international, and multicultural city with constant exchange and contacts across cultures. This is particularly so in a description that the Franciscan friar William of Rubruck made while visiting Qaraqorum in the year 1254. Rubruck noted that Muslim traders, Chinese craftsmen, Buddhists, Nestorian Christians as well as several European captives all lived and worked in Qaraqorum. Despite this, the city is seldom included on maps depicting Eurasian and Inner Asian travel and trade networks of the 13th–14th century. Such networks have left archaeological traces at various city sites, through the presence of imported ceramics, food, and other goods. This article will focus on the glazed ceramics excavated in Qaraqorum. The author classified the material and determined the production sites of the different wares. A chorological study based on this data expands our knowledge of connections to Qaraqorum in the medieval Asian trade network. The results are presented in this article. As every aspect of archaeological research reflects parts of the overall picture only, this study is meant to enable further research on the subject. This article is dedicated to the symposium “800 years Qaraqorum” and thus included in a broader research framework on the fascinating Old Mongolian capital.